Analisis Pengaruh Upah Dan Modal Terhadap Penyerapan Tenaga Kerja Pada Usaha Kecil Menengah Industri Laundry Di Kota Surabaya - Yeskri Meikel Davidson Mamuaya; Gigih Pratomo (Economie: Jurnal Ilmu Ekonomi, 2020)
The writing in this thesis takes the topic of comparison of absorption of labor laundry company in the city of Surabaya with a benchmark wage and capital. This research aims to find out how big the influence of wages and capital against labour absorption in the small and medium industrial laundry business in the city of Surabaya. Labor absorption is an act of the company in the demand for labor, where labor will do or carry out work that provided the company in accordance with the areas of the company. So in this case, the workforce will be awarded the work related to the field of laundry. Methods of analysis used in this research is unstructured/undated. The results of sports data that has been done is not to wage labour, whereas the absorption of capital effect on the absorption of labour.